THE IMPACT OF SCHOOL FEEDING PROGRAMMEME ON ENROLMENT IN PRIMARY SCHOOLS IN ARID AND SEMI-ARID AREAS. A CASE OF KATHONZWENI SUB-COUNTY, MAKUENI COUNTY, KENYA - James, Mbondo Kitaka; Kathuri, Prof. Nephat J.; Kibaara, Dr. Tarsilla. M. (IJRDO- Journal of Educational Research, 2017)
Providing school meals can play a critical role in ensuring that children learn well. Many children from poor homes go to school hungry. This leads to poor concentration in class. This study sought to determine the impact of the School Feeding Programme (SFP) on enrolment in primary schools in Arid and Semi-Arid Areas, taking a case of Kathonzweni Sub-County, Makueni County, Kenya. Based on the findings of the study, SFP had a high influence on enrolment of children into primary schools in Kathonzweni Sub-County. The study established that SFP greatly influenced school attendance by pupils in Kathonzweni Sub-County. They had a significant effect on retention of pupils in the learning process. The study also revealed that challenges facing school heads in the course of implementing the school feeding programme included: late funds disbursement, parent’s failure to pay funds to cater for the cook, water and firewood shortage. It was therefore recommended that the financiers of the SFP should ensure that enough funds were released in time to give schools’ management enough time to purchase enough food stuffs in time.